Special FDA designations for drug development: orphan, fast track, accelerated approval, priority review, and breakthrough therapy - Michaeli, Daniel; Michaeli, Christoph T.; Albers, Sebastian; Boch, Tobias; Michaeli, Julia (The European journal of health economics, 2024)
Over the past decades, US Congress enabled the US Food and Drug Administration (FDA) to facilitate and expedite drug development for serious conditions filling unmet medical needs with five special designations and review pathways: orphan, fast track, accelerated approval, priority review, and breakthrough therapy.